Antibacterial activity of Trigonella Foenum- groecum essential oil against skin infection with Staphylococcus aureus: In vitro and in vivo studies - Abu-Raghif, Ahmed Rahma (AL-Kindy College Medical Journal, 2016)
Background: Multi- drug resistant (MDR) Staphylococcus aureus infections have become a major public health concern in both hospital and community settings.Objective: to investigate the antibacterial activity of T. Foenum- groecum essential oil against skin infection with S. aureus and to study probable synergistic activity in combination with Clindamycin.Type of the study: Cross-sectional study. Methods: Antibacterial activity of T. Foenum- groecum essential oil extract (1.2gm/100 µl) was investigated in multi- drug resistance (MDR) Staphylococcus aureus specimen isolated from patients with skin infection in Baghdad. T. Foenum- groecum use externally for cellulites and skin inflammation due to the presence of diosgenin .fast liquid chromatography was used to separate these components. Results: Antibiotics combinations revealed that T. Foenum- groecum essential oil with Clindamycin against MDR isolates of S. aureus showed a synergistic effect when used as 1/4 MIC for each antimicrobial. In vivo study was executed to determine antibacterial activity of these compounds by induction of skin infection with Staphylococcus aureus in mice and the treatment begun after 4hrs later and continue to seven days then skin biopsy was taken and sent for histopathological examination. Conclusions: According to the results of this study, we can conclude that T. Foenum- groecum essential oil has remarkable antistaphylococcal activity. Combination of T. Foenum-groecum essential oil with Clindamycin was more effective than Clindamycin alone in treatment of skin infection with Staphylococcus aureus.